Efektivitas Pembelajaran Berdiferensiasi dalam Meningkatkan Hasil Belajar Siswa: Studi pada SMP Negeri 2 Sakra - Ilna Anisa; Lilik Nurindah Sari; Widiyan Lestari; Lalu Muhammad Nurul Iman (Alpatih Harapan Semesta, 2026)
This study aims to analyze the implementation of student-centered learning in order to improve learning outcomes at SMPN 2 SAKRA. The background of this research arises from the observation that there are differences in students' academic abilities within the classroom, requiring teachers to apply learning strategies that can accommodate this diversity. The research uses a qualitative approach, and data collection techniques include observation, interviews, and document analysis. The findings show that learning adjustments are carried out through grouping students based on their understanding levels, providing materials and tasks in stages, and using varied teaching methods. The application of student-appropriate learning has been found to effectively increase student participation, learning motivation, and overall academic performance. Therefore, learning that is adjusted to students' abilities can serve as an effective alternative strategy to enhance the quality of the learning process and outcomes.